Analisis Kondisi Daerah Resapan Air Kecamatan Sukasada Kabupaten Buleleng Menggunakan Sistem Informasi Geografis - NURLELY LAMPITA PANDIANGAN; I WAYAN DIARA; TATI BUDI KUSMIYARTI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Analysis of Watersheds Condition in Sukasada District, Buleleng Regency Using Geographic Information System Water catchment areas are areas where water is released into the soil. The research area has various determinants of water absorption conditions to allow the conditions of the water catchment area to vary. This study aims to determine the state of the water catchment area in Sukasada District and draw up a map of the water catchment area in Suksada District. This research was conducted from July 2020 to October 2020. The method used in this study was the evaluation and overlay using the Geographical Information System. The required parameters are soil type, land use, slope, and precipitation. The results showed that the status classes of the catchment areas were good, naturally normal, critical, somewhat critical, and very critical. The water infiltration status in the study area was dominated by the natural normal class with 3,972 ha (32%), followed by very critical classes with 3,906 ha (24%), more good classes with 3,584 ha (21%), the critical class with 2,165 ha (13%) and the smallest, the somewhat critical class with 1.808 ha (10%).